Efficient image encryption scheme based on generalized logistic map for real time image processing - Shah, Asif A.; Parah, Shabir A.; Rashid, Mamoon; Elhoseny, Mohamed (Journal of real-time image processing, 2020)
In this era of the information age with digitalization, the transmission of sensitive real-time image information over insecure channels is highly-likely to be accessed or even attacked by an adversary. To prevent such unauthorized access, cryptography is being used to convert sensitive information in real-time images into unintelligible data. Most of the time, schemes are proposed with a high level of security. However, the challenge always remains the slower speeds due to their high complexity which makes them unusable in the applications of real-time images. In this paper, an efficient image encryption algorithm has been developed and tested for real-time images. The proposed scheme makes use of encryption with an efficient permutation technique based on a modular logistic map to bring down the size of the chaotic value vector, required to permute real-time image. We show that an efficient permutation is obtained using only N chaotic numbers for a square image with 3 N pixels ( N Pixels in each color bit plane). The algorithm makes use of a 192-bit key; divided into smaller blocks and each block selected chaotically to diffuse the pixel using multiple XOR operations. The experimental analysis reveals that the proposed algorithm is immune to various statistical and differential attacks such as entropy, histogram analysis, spectral characteristic analysis, etc. A comparison of the proposed scheme with some state-of-the-art techniques show that it performs better, and as such, can be utilized for efficient real-time image encryption.